Investigating the link between trait procrastination and college students’ sleep quality: the mediating role of self-efficacy and executive function - Wang, Yan; Chong, You; Men, Ruixue; Li, Fei; Pan, Hongbing; Xu, Xuan (Frontiers in Psychiatry, 2026)
PurposeAs a personality trait characterized by an irrational tendency to avoid, trait procrastinators usually have poor time management. When they face the dilemma of stopping to sleep or working inefficiently under the threat of deadlines, they usually make difficult choices, leading to poor sleep. The purpose of this study is to explore the comprehensive effects of trait procrastination, self-efficacy and executive function on the sleep quality of college students, and to investigate the mediating role of self-efficacy and executive function.Material and methods745 college students were surveyed using the short version of the General Procrastination Scale, General Self-Efficacy Scale, Chinese version of Geurten Executive Function Questionnaire and the Pittsburgh Sleep Quality Index. Descriptive statistics, correlations analysis and multicollinearity diagnosis were conducted. To test the proposed hypotheses, a chain mediation model was built, and a bootstrap analysis was conducted using Process 4.2 in the SPSS macro program.Results1) Trait procrastination significantly negatively predicted sleep quality. 2) Self-efficacy mediated the relationship between trait procrastination and sleep quality. 3) Executive function mediated the relationship between trait procrastination and sleep quality. 4) Self-efficacy and executive function played a chain mediation role between trait procrastination and sleep quality. 5) When self-efficacy acted as the sole mediating factor, there was a masking effect.ConclusionA higher level of trait procrastination was associated with lower self-efficacy, impaired executive function, and poorer sleep quality, suggesting that trait procrastination adversely affects not only mental health but also higher-order cognitive and physiological functions. Self-efficacy weakened or masked the direct relationship between trait procrastination and sleep quality. These findings offer valuable insights into the dual protective role of self-efficacy against trait procrastination affecting sleep quality. Interventions aimed at improving executive function have great potential to enhance the sleep quality of college students with procrastination problems.